The Effect Number of Members, Savings, and Loans on Remaining Operating Result (SHU) with Working Capital as a Moderating Variable: A Study of KPRI Tegal City - Anggi Dwi Agustina; Abdulloh Mubarok; Fahmi Firmansyah (JABKO: Jurnal Akuntansi dan Bisnis Kontemporer, 2026)
Cooperative performance, as reflected in the Remaining Operating Results (SHU), is influenced by various internal factors, including the number of members, savings, and loans. This study examines the relationship between these three variables and SHU, while also evaluating the role of working capital as a moderating variable in the Employee Cooperatives of the Republic of Indonesia (KPRI) registered with the Central Cooperative of the Republic of Indonesia Employees (PKPRI) in Tegal City during the 2021–2025 period. Using a quantitative approach, this research employed secondary data obtained from 23 KPRI. A saturated sampling technique resulted in 115 observations, which were analyzed using multiple linear regression and moderated regression analysis with SPSS version 22. The findings indicate that the number of members and savings have a significant positive effect on SHU, whereas loans do not have a significant positive effect on SHU. The moderation analysis reveals that working capital strengthens the relationship between the number of members and SHU but is unable to moderate the effects of savings and loans on SHU. These findings highlight the importance of optimizing the management of membership, savings, loans, and working capital to enhance cooperative performance.